Processamento e propriedades do sistema ferroelétrico (Li,K,Na)(Nb,Ta)O3 dopado com CuO - Zapata, Angélica Maria Mazuera (2015)
The search for new lead-free piezoelectric materials has been a major goal of many scientists in recent years. The main cause is the replacement of widely used lead zirconate titanate (PZT) based ceramics due to the highly toxic characteristics of the lead element. Potassium sodium niobate based ceramics have shown high piezoelectric coefficients and a morphotropic phase boundary close to the composition (K0.5Na0.5)NbO3 (KNN), similar to that found in lead zirconate titanate. However, the preparation of highly dense KNN based ceramics is extremely difficult. In this work, the structural, mechanical and electrical properties of lead free ferroelectric ceramics with compositions Li0,03(K0,5Na0,5)0,97Nb0,8Ta0,2O3 + xwt% CuO (x = 0; 2 and 3.5) were studied. All the compositions, sintered at 1050ºC for 2 hours had high density, approximately 95% of the theoretical value. Rietveld refinement of the X ray diffraction patterns showed a mixture of both orthorhombic Bmm2 and tetragonal P4mm phases, for all compositions. Nevertheless, compositions with high CuO contents have mainly the tetragonal phase. Dielectric and dynamic mechanical analysis (DMA) measurements showed two polymorphic phase transitions with increasing temperature. Both phase transitions have diffuse character and they can be related with the transformation of the orthorhombic phase fraction in the tetragonal one, and with the transformation of the tetragonal ferroelectric phase to a cubic paraelectric one. The origin of the difference observed between the temperatures where both techniques, dielectric and mechanical, see the diffuse phase transition is discussed. The ceramic with 2wt% of CuO is electrically softer than the other compositions and it has the highest value of the piezoelectric coefficient d31. Also, in this work we studied the possibility of using high contents of CuO to promote the formation of liquid phase for obtaining and extracting single crystal seeds, which can be used for the texture of KNN-based ceramics. The ceramic Li0,03(Na0,5K0,5)0,97Ta0,2Nb0,8O3 + x wt% CuO with x=16, sintered at 1090ºC for 2 hours, is a perfect candidate for extracting grains which may be used as seeds. Furthermore, ceramics with x=13, sintered at 1110ºC for 2 hours, showed a partial melting of the material, which caused the growth of highly oriented grains. This material can be practically considered as a single crystal and, with a proper cut procedure, the desired single crystal seeds can be obtained. This method to obtain single crystal seeds, as proposed in this work, is very simple and novelty.